Hunian Vertikal Moskow, Rusia dalam Perspektif Ekonomi Politik Perkotaan - Zainuddin Losi; Wandi Abbas (Universitas Islam Darul Ulum Lamongan, 2025)
The dominance of vertical housing in Moscow often raises questions, especially when compared to Russia's vast land availability. This article analyzes why Moscow is dominated by highrise buildings and minimal landed housing, such as bungalows or terraced houses. Using an urban political economy approach and historical-institutional analysis, the article shows that the pattern of vertical housing in Moscow is a result of the legacy of Soviet-era housing policies, political-economic centralization, land ownership regimes, and post-Soviet urban development strategies. The study argues that the limitation of horizontal housing in Moscow is not a matter of national land availability but rather a matter of spatial politics, the logic of state power, and the dynamics of Russian state capitalism. These findings contribute to the comparative study of non-Western urban development and offer new perspectives on housing in post-socialist countries.